The Effect of Stretching Exercises on Perceived Discomfort, Trunk Muscle Activity, and Fatigue in Prolonged Sitting Tasks - Maryam Mohammadalizadeh; Zeinab Kazemi; Ehsan Garosi; Ahmadreza Keihani; Alireza Shaghaghi; Mohammad Sadegh Ghasemi (بهداشت و ایمنی کار, 2023)
Introduction: Prolonged sitting postures are among the risk factors for musculoskeletal disorders in occupational settings, leading to increased musculoskeletal discomfort in various body regions. This discomfort can negatively impact individuals’ health and impose high costs on society in terms of work absences, early disabilities, and reduced productivity. The purpose of this study is to investigate the effect of stretching exercises on the level of discomfort, muscle activity, and muscle fatigue in the neck and trunk region during prolonged sitting tasks. Material and Methods: This experimental study was conducted among 20 healthy male and female participants under two test conditions: control and intervention. In the control condition, participants performed cognitive tasks (watching videos, typing, text editing, and nback cognitive test) without any intervention. In the intervention condition, participants performed stretching exercises before each task. The Visual Analogue Scale was used to assess perceived discomfort. Also, muscle fatigue was evaluated using an electromyography (EMG) device and RMS and MPF measures. Results: Discomfort in hands and arms (p-value=0.04) and lower back (p-value=0.03) during video-watching was higher in the control condition than in the intervention. Regarding muscle activity, the activity of the right cervical erector spinae during the video-watching task was lower in the control condition than in the intervention. In the n-back cognitive test and text editing, the right lumbar erector spinae muscle activity was significantly higher in the control condition than in the stretching exercises intervention. Regarding the left cervical erector spinae, a significant difference was observed between fatigue in control and intervention conditions during the video-watching task. Also, right thoracic erector spinae fatigue in text editing was higher in the control condition than in the exercise intervention; however, for the n-back test, the level of fatigue was lower in the control condition compared to the intervention. Conclusion: The perceived discomfort in seated computer tasks is generally lower in the exercise intervention compared to the control condition. The stretching exercises used in this study improved muscle activity and reduced fatigue in some of the trunk muscles, although the effects of the exercises depend on the type of task. Overall, muscle fatigue in two cognitive tasks, text editing and n-back, was more affected by stretching exercises than other tasks.